Lungensonografie bei Patienten mit Verdacht auf COVID-19 – Schritt-für-Schritt - Schmid, Bonaventura; Hornuß, Daniel; Feuerstein, Doreen; Schultheiß, Michael; Damjanovic, Domagoj (DMW - Deutsche Medizinische Wochenschrift, 2020)
Pulmonary sonography can be a valuable aid in the differential diagnosis of a variety of cardiopulmonary diseases, including patients with COVID-19. Pulmonary sonography is an examination method that is also quickly available at the bedside without additional risks for the patient. When COVID-19 is suspected, lung sonography is a valuable component of initial diagnosis when used systematically, performed hygienically and correctly. However, the findings of pulmonary sonography must be placed in the clinical context; sonography does not replace the gold standard of PCR diagnosis. The article shows how this sonography is performed and which findings in COVID-19 are relevant.
Keywords: Ersteinschätzung; Interkostalräume; subpleurale Konsolidierungen; fokussierte Echokardiografie; SARS-CoV-2